Multimodal Interventions to Prevent and Control Carbapenem-Resistant Enterobacteriaceae and Extended-Spectrum β-Lactamase Producer-Associated Infections at a Tertiary Care Hospital in Egypt - Noha A. Kamel; Khaled M. Elsayed; Mohamed F. Awad; Khaled M. Aboshanab; Mervat I. El Borhamy (MDPI AG, 2021)
The current rise of multidrug-resistant (MDR) Gram-negative Enterobacteriaceae including the extended-spectrum β-lactamase (ESBL)-producing organisms and carbapenem-resistant Enterobacteriaceae (CRE) has been increasingly reported worldwide, posing new challenges to health care facilities. Accordingly, we evaluated the impact of multimodal infection control interventions at one of the major tertiary healthcare settings in Egypt for the aim of combating infections by the respective pathogens. During the 6-month pre-intervention period, the incidence rate of CRE and ESBL-producing clinical cultures were 1.3 and 0.8/1000 patient days, respectively. During the post-intervention period, the incidence of CRE and ESBL producers continued to decrease, reaching 0.5 and 0.28/1000 patient days, respectively. The susceptibility rate to carbapenems among ESBL producers ranged from 91.4% (ertapenem) to 98.3% (imipenem), amikacin (93%), gentamicin (56.9%), and tobramycin (46.6%). CRE showed the highest resistance pattern toward all of the tested β-lactams and aminoglycosides, ranging from 87.3% to 94.5%. Both CRE and ESBL producers showed a high susceptibility rate (greater than 85.5%) to colistin and tigecycline. In conclusion, our findings revealed the effectiveness of implementing multidisciplinary approaches in controlling and treating infections elicited by CRE and ESBL producers.